Sensors, Imaging Agents, and Theranostics to Help Understand and Treat Reactive Oxygen Species Related Diseases - Yan, Kai‐Cheng; Sedgwick, Adam C.; Zang, Yi; Chen, Guo‐Rong; He, Xiao‐Peng; Li, Jia; Yoon, Juyoung; James, Tony D. (Small methods, 2019)
Reactive oxygen species (ROS) consist of a diverse range of oxidative small molecular ions and free radicals that are produced throughout the body during certain biological processes. Due to their high reactivity, these molecules result in the damage of tissues and cells. Therefore, ROS have been implicated in an array of diseases including cancer, inflammation, and neurodegenerative diseases such as Parkinson's disease and Alzheimer's disease. Owing to the simplicity, sensitivity, and selectivity of fluorescence‐based strategies, many small‐molecular sensors or imaging agents have been developed to sense and visualize ROS both in vitro and in vivo. Likewise, activatable drug delivery and prodrug systems that can be triggered by ROS for disease theranostics (diagnostic and therapeutic combined) have been developed. Herein, recently developed fluorescence‐based sensing and imaging agents for the detection of ROS both intracellularly and in vivo are summarized. In addition, drug delivery, which require activation by ROS to achieve disease theranostics is also discussed. Reactive oxygen species (ROS) are vital for a myriad of biological processes, and mounting evidence has suggested their crucial role for the progression of some serious diseases. Here, state‐of‐the‐art fluorescent probes to understand ROS‐relevant diseases are summarized. Functional materials or prodrugs activatable by endogenous ROS or by light activation of photosensitizers to produce ROS for disease theranostics are also discussed.